60 GHz on-chip antenna array with efficiency improvement using 3D microfabrication technology - Zamith, M. (2015)
The 55-65 GHz band has very interesting characteristics, such as allowing high-bandwidth communications and improved security (due to high absorption). From the antenna point of view, it also has the interesting feature of allowing the fabrication of very small antennas. Because they're so small, these antennas can be placed directly on-chip. However, silicon is a high loss material at such high frequencies. This paper proposes a solution to obtain one antenna array with improved efficiency. Instead of designing the antennas on top of silicon, 3D antennas are designed to lie above the silicon substrate.